Social Gradients in Employment during and after the COVID-19 Pandemic - Annette Alstadsæter; Bernt Bratsberg; Simen Markussen; Oddbjørn Raaum; Knut Røed (Institute of Labor Economics (IZA), 2023)
We examine employment effects of the COVID-19 crisis in Norway during the initial lockdown, through the subsequent recovery, and after the dust had settled. While we identify large and socially skewed effects of the crisis through its early phases, we find no long-term effects on employees exposed to early risk of job loss. For those employed at the onset of the pandemic, both the level and the socioeconomic composition of employment quickly returned to normal. In contrast, we find considerable negative long-term employment effects on people who were non-employed when the crisis hit. We argue that these patterns can be explained by social insurance policies that gave priority to protecting existing jobs and to distribute benefits to those who were temporarily laid off. Given the extreme increase in the social insurance caseload, an almost unavoidable side-effect was reduced capacity for providing services to the already non-employed.
Keywords: E24; J2; J4; J6; J11; 330; labor demand shock; COVID-19; employment; social gradient